2015
DOI: 10.1371/journal.pone.0128688
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Specific Selection in Three Domestic Sheep Breeds

Abstract: BackgroundCommercial sheep raised for mutton grow faster than traditional Chinese sheep breeds. Here, we aimed to evaluate genetic selection among three different types of sheep breed: two well-known commercial mutton breeds and one indigenous Chinese breed.ResultsWe first combined locus-specific branch lengths and di statistical methods to detect candidate regions targeted by selection in the three different populations. The results showed that the genetic distances reached at least medium divergence for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 91 publications
1
45
0
1
Order By: Relevance
“…The regions displaying autozygosity in dairy sheep breeds were linked mostly with genes involved in reproduction, such as the CCNB2 gene, which affects oocyte development (Wang et al . ). Other candidate genes detected within these ROH islands were TYRP1 , which is involved in controlling coat pigmentation in sheep and has a homolog on bovine chromosomes 2 and 8, on which the location of QTL for milk traits has been reported (Ashwell et al .…”
Section: Resultsmentioning
confidence: 97%
“…The regions displaying autozygosity in dairy sheep breeds were linked mostly with genes involved in reproduction, such as the CCNB2 gene, which affects oocyte development (Wang et al . ). Other candidate genes detected within these ROH islands were TYRP1 , which is involved in controlling coat pigmentation in sheep and has a homolog on bovine chromosomes 2 and 8, on which the location of QTL for milk traits has been reported (Ashwell et al .…”
Section: Resultsmentioning
confidence: 97%
“…It is responsible for remodeling proteins that maintain the structure of skeletal muscle [16,17]. Another PCR study has reported significant genetic variants in Myocyte enhancer binding factor 2B (MEF2B) and Thyrotropin releasing hormone degrading enzyme (TRHDE) genes affecting body weight and growth in sheep [18][19][20]. For instance, SNPs have been detected in MEF2B and TRHDE genes associated with sheep body weight and chest girth [20].…”
Section: Genes Associated With Growth and Body Weightmentioning
confidence: 99%
“…In addition to growth and body weight traits, body mass index and body size traits are also an important sheep production traits. A genome wide specific selection study has identified Fat mass and obesity-associated protein (FTO) and Apolipoprotein B Receptor (APOBR) genes affecting body mass index in German mutton merino, CMF, and African white dorper sheep breeds [18]. FTO is part of the alpha-ketoglutarate-dependent hydroxylase gene family, which is a non-heme iron-containing protein.…”
Section: Genes Associated With Growth and Body Weightmentioning
confidence: 99%
See 2 more Smart Citations